2020
DOI: 10.1515/ntrev-2020-0073
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon polymerization nanolithography technology for fabrication of stimulus-responsive micro/nano-structures for biomedical applications

Abstract: Micro/nano-fabrication technology via two-photon polymerization (TPP) nanolithography is a powerful and useful manufacturing tool that is capable of generating two dimensional (2D) to three dimensional (3D) arbitrary micro/nano-structures of various materials with a high spatial resolution. This technology has received tremendous interest in cell and tissue engineering and medical microdevices because of its remarkable fabrication capability for sophisticated structures from macro- to nano-scale, which are dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 161 publications
(164 reference statements)
0
50
0
1
Order By: Relevance
“…MPP in prior studies has repeatedly demonstrated nanoscale print size, suc the aforementioned vat polymerization methods significantly in ultra-high re [124,125]. An example of this is a synthetic nanoporous geomaterial fabricated wi as illustrated in Figure 22, which shows an electron microscope image of a 150 μ of replica shale rock with a minimum feature size of 160 nm [15].…”
Section: Multi-photon Polymerization (Mpp)mentioning
confidence: 95%
“…MPP in prior studies has repeatedly demonstrated nanoscale print size, suc the aforementioned vat polymerization methods significantly in ultra-high re [124,125]. An example of this is a synthetic nanoporous geomaterial fabricated wi as illustrated in Figure 22, which shows an electron microscope image of a 150 μ of replica shale rock with a minimum feature size of 160 nm [15].…”
Section: Multi-photon Polymerization (Mpp)mentioning
confidence: 95%
“…Still, regarding the employed samples in the TPP experiments, photoinitiator compounds are essential to the technique. Many groups have been working on the development or testing of new photoinitiators for TPP experiments [ 72 , 73 ]. Usually, they look for compounds with a high value of TPA cross-section ( ).…”
Section: Two-photon Polymerization (Tpp) Fundamentalsmentioning
confidence: 99%
“…There are, therefore, plenty of possibilities to develop biomimetic responsive microstructures. The literature is vast: we will provide only recent examples on 3D photo-polymerized hydrogels, leaving more exhaustive analysis to previous reviews [ 133 , 134 , 135 ].…”
Section: Laser-fabricated Active Microstructured Hydrogelsmentioning
confidence: 99%